Overview of Real-Time PCR Principles - Seifi, Morteza; Ghasemi, Asghar; Heidarzadeh, Siamak; Khosravi, Mahmood; Namipashaki, Atefeh; Soofiany, Vahid Mehri; Khosroshahi, Ali Alizadeh; Danaei, Nasim (IntechOpen, 2012)
None